Variations in Ageing in Home and Ageing in Neighbourhood. Issue 2 (3rd April 2017) - Han, Jung Hoon; Kim, Jun-Hyung
ABSTRACT: This paper takes a new approach to investigating people who age in place. It provides an explanation for why people age in a place that can be useful in government and corporate planning. Our research investigates the principal factors that drive the decision of a rising number of older Australians to age in place. Many older people wish to age in place rather than move in with their children or be institutionalised. They wish to continue to be active in their local communities and maintain their existing social ties. The concept of ageing in place covers two distinct groups: those who are able to stay in their current dwellings and age in home and those who move house but remain in their local community and age in neighbourhood. Age-friendly home modification is a response to ageing in home, whereas the provision of institutional healthcare and the provision of age-suitable housing to facilitate downsizing are associated with ageing in neighbourhood. Using Household, Income and Labour Dynamics in Australia (HILDA) survey data, this research examines the mobility decisions of older Australians and identifies the major determinants of a decision to age in place. This research argues for a better understanding of ageing in place, differentiating between those ageing in home and those ageing in neighbourhood.